Fish Protein Concentrate Fortification Siam Patin on Amplang Snack Products and Mi Sago Instant Product as a Leading Regional Riau - Dewita Buchari; - - Syahrul (Jurnal Pengolahan Hasil Perikanan Indonesia, 2014)
To enhance fish consumption in the community especially children, fortification on processed fish product is conducted. The processed fish products are developed to fill the requirements as the fish based food products that own characterizations such as ready to eat, easy to carry, and less time to cook. Amplang snacks and instant sagoo noodles are defined as the products that fills the requirements. The research was aimed to process catfish into fish protein concentrate to become amplang snack and instant sagoo noodles. These products were designed as the effort to develop the local priority products in Riau by using diversification and fortification methods. Experimental method with fortification treatments on Fish Protein Concentrate (FPC) extract from Catfish that generate products of amplang snacks and instant sagoo noodles and fish tofu were carried out. The fortified products were examined by organoleptics test that involved panelists. The results showed that the proximate analysis on fortified Catfish Protein Concentrate products were presented as following :1). water contents of 3,13 %, ash of 2,85 %, protein content of 16,13 % and fat content of 18, 66 % for ampang snacks; and 2). water contents of 11,77 %, ash of 1,30 %, protein content of 12,35 % and fat content of 1,86 % for instant sagoo nodles. All fortified FPC products filled the Indonesian Nasional Standard (SNI).Keywords: Fortification, Catfish, and Fish Protein Concentrate